Anti-hypertensive medication adherence, socioeconomic status, and cognitive aging in the Chinese community-dwelling middle-aged and older adults ≥ 45 years: a population-based longitudinal study - Chenglong Li; Daijun He; Yufan Liu; Chao Yang; Luxia Zhang (BMC Medicine)
Abstract Background It remains unclear whether anti-hypertensive medication use is associated with cognitive aging in general Chinese middle-aged and older adults, as well as the interplay with socioeconomic status (SES). We aim to examine associations of anti-hypertensive medication adherence, SES, and cognitive aging in Chinese middle-aged and older adults. Methods Our study was based on the China Health and Retirement Longitudinal Study, an ongoing longitudinal national survey recruiting community-dwelling adults aged ≥ 45 years. Baseline anti-hypertensive medication use was assessed at wave 1. Longitudinal adherence to anti-hypertensive medication was assessed during waves 1 and 2. SES was assessed using income, education, employment, and medical insurance. The annual rate of cognitive change was assessed using cognitive Z scores. Linear mixed models were used to examine longitudinal associations. Results A total of 9229 participants were included (mean [SD] age: 57.1 [8.9] years; men: 50.8%). After controlling for blood pressure and other characteristics, participants taking anti-hypertensive medication at baseline, compared to participants not using medication, had a significantly decelerated decline in global cognition (β = 0.014; 95% confidence interval [CI], 0.003 to 0.025 SD/year; P = 0.01) and memory (β = 0.021; 95% CI, 0.008 to 0.034 SD/year; P = 0.001), respectively. Similarly, participants with high anti-hypertensive medication adherence during follow-up had slower declines in global cognition (β = 0.014; 95% CI, 0.002 to 0.027 SD/year; P = 0.02) and memory (β = 0.023; 95% CI, 0.008 to 0.038 SD/year; P = 0.003), compared to the low adherence group. There were no significant differences in cognitive decline between hypertension participants using or persistently adhering to medication and normotension participants. The SES significantly interacted with anti-hypertensive medication in associations with cognitive aging, with more evident associations observed in low SES subgroup (all P for interaction < 0.05). Several sensitivity analyses were conducted, observing consistent findings. Conclusions Adhering to anti-hypertensive medication was associated with decelerated cognitive aging in Chinese community-dwelling middle-aged and older adults, especially in participants with low SES. These findings indicate that promoting anti-hypertensive medication use could be important to achieve healthy and inclusive cognitive aging in general Chinese middle-aged and older adults living with hypertension.